Kontribusi Remaja Masjid dalam Menumbuhkan Sikap Religius di Masjid Al-Muflihin Bandar Selamat - Arlina, Arlina; Ananda Sholih Nasution; Della Latifah Amanda; Nanda Ayuningtyas; Salamat Riadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to obtain information regarding the contribution of teenagers from the Al-Muflihin mosque in cultivating religious attitudes. The data in this research uses qualitative data, with data collection techniques in the form of observation, interviews and documentation used to collect and strengthen research data. The research subjects were mosque teenagers. The data analysis technique uses the Milles and Huberman models. With data validity techniques in the form of lingering and lengthy, as well as triangulation. The research results showed that the contribution of the mosque's youth was mostly carrying out religious activities so that it could foster religious attitudes in teenagers in the mosque's youth organization.